THE INTERRELATION OF MORAL CONSCIOUSNESS, MORAL PRACTICE, AND MORAL RELATIONS WITHIN THE SYSTEM OF MORALITY AND THEIR SIGNIFICANCE AS FUNDAMENTAL ELEMENTS. - Sunatov Dilshod Hoshimovich (International Journal of Literature and Language Studies, 2026)
This article provides a theoretical and analytical examination of the key structural components of morality, namely moral consciousness, moral practice, and moral relations. Moral consciousness is interpreted as a system of internal spiritual and ethical criteria that regulate human behavior within society. Moral practice is understood as the real-life manifestation of values, norms, and virtues formed within moral consciousness. In addition, moral relations are analyzed as a system of ethical interactions between individuals and social groups. These three components are mutually interconnected and collectively constitute the holistic structure of morality, playing a significant role in the moral and spiritual development of society.